The Cascading of Contrast Effects on Auditors' Judgments in Multiple Client Audit Environments - Bhattacharjee, Sudip; Maletta, Mario J.; Moreno, Kimberly K. (The Accounting Review, 2007)
Accounting decisions often involve similar types of judgments regarding different clients, projects, or employees. These tasks may use similar information items and be performed within the same work session. While independent consideration of the information for each respective decision may be desired, psychology research on contrast effects suggests that the information from a previous decision may be retained and compared to the information provided for a current judgment. Such contrast effects are potentially critical to accounting judgments because they suggest that the information associated with a given decision task will be evaluated differently depending on the nature of the prior contextual information. Using a multi-client audit context, we find that auditors are susceptible to contrast effects such that their judgments on a current client are influenced by their exposure to similar judgment information on a prior client. We also extend prior psychology and accounting research by examining and finding that for a current client, the magnitude of the contrast effect from an initial judgment task cascades to influence indirectly related subsequent judgment tasks for which no information from the prior client is available for comparison. We also find auditors' documentations of evidence are systematically affected by the contrast and cascading of contrast effects. Thus, our results provide support for contrast effects and, most important, the cascading of contrast effects to subsequent decisions.